Research on the Integration Mechanism of New National System and Market Mechanism - Xiang, Shaoxin (Economics & Management Review, 2025)
This study explores in depth the integration mechanism of the new national system and market mechanism under the conditions of socialist market economy. The "novelty" of the new national system lies in its complementary and collaborative relationship with market mechanisms, rather than a simple replacement. The research constructs an analytical framework from three levels: theoretical logic, practical path, and challenge response, systematically analyzing the integration mechanism of the two in four dimensions: strategic orientation, resource allocation, organizational mobilization, and innovation ecology. Research has shown that the new national system is a new institutional arrangement and organizational model that organically combines government, market, and social entities. Its effective integration with market mechanisms is the key to solving the bottleneck problem of key core technologies and improving the overall efficiency of the national innovation system. In response to the problems of blurred boundaries, poor collaboration, and incompatible incentives in the current integration process, this article proposes optimization paths such as clarifying the boundary between government and market roles, innovating collaborative organizational models, and deepening scientific and technological system reforms, providing theoretical support and practical reference for key core technology research and development under the conditions of a sound socialist market economy.